Entorno virtual de aprendizaje para el desarrollo de contenidos en la asignatura aplicaciones ofimáticas para tercer año de bachillerato informática. - Alburqueque Atariguana, Dayana Madelay; Bayas Gia, Arlis Daniela (Machala, Utmachala, 2023)
This research is focused on the implementation of an EVA for interactive teaching of the subject office applications, which is designed in the Canvas Lms application, taking into account the motivation that this generates in students through application in the PEA. The research was directed to the students of the third year of high school computer science parallel "A" of the Carmen Mora de Encalada high school in the city of Pasaje, El Oro province. That said, it was decided to conduct a qualitative and quantitative research with descriptive scope. The instruments used to evaluate the effectiveness of the resource and development in the classroom was the application of a survey, addressed to both teachers and students, thus achieving the expected results of a favorable acceptance. With the execution of this research report it has been proposed to diagnose the impact of the correct use of an EVA in the potentiation of the PEA, in addition to a significant learning in the students, where they will be evaluated and obtain the necessary information about the contents of the subject and a direct interaction with the teacher, therefore generating motivation and interest in the discovery of the different activities hosted in the virtual environment, this in the area of computer science in the third year of high school. For this reason, the tools used by the educator in the instruction of the subject office automation applications in the third year of high school computer science were identified in order to establish the appropriate resources to adapt them later in the environment proposed by the research. For this purpose, the design of the contents and structuring of the subject office automation applications in the Canvas LMS platform was carried out considering important aspects that favor the educational process, giving importance to the teacher's planning and the best development and interaction in the classes, generating self-learning in the students. It is worth mentioning that the methodology used for the execution of the prototype was the PACIE methodology, which involves the use of ICTs for the benefit of meaningful learning, strengthening the content and knowledge provided with it. Consequently, a survey and interview was conducted with the teacher This first interaction was carried out in person with the participation of the teacher in charge of the subject office automation applications of the institution where the research was carried out, a survey was used as an instrument with the objective of knowing aspects and suggestions in order to improve the design, structure, content and images in the Eva for the prototype, The survey was used as an instrument to know aspects and suggestions in order to improve the design, structure, content and images in the Eva for the interaction with the students where the structure and information stored in the proposed Eva was made known, in addition to the activities proposed in the environment with the objective of improving the development of contents in the subject, to determine the improvements that can be implemented to the digital resource, to later apply it to the students, through a demonstrative class with the different activities implemented in the EVA. After the first experience with the teacher of the subject Office Applications, the different aspects to be improved were taken into account to then perform the second interaction with the students of third year of computer science, where a demonstration of the functionalities of EVA in the Canvas LMS platform was performed, so that according to the results obtained it was possible to identify the effectiveness of the use of EVA in the subject and with this the students responded in favor of the implementation of the resource in the subject thus achieving the expected results of a favorable acceptance.
La presente investigación está enfocada en la implementación de un EVA para la enseñanza interactiva de la asignatura aplicaciones ofimáticas, el cual está diseñado en la aplicación Canvas LMS, teniendo en cuenta la motivación que este genera en los estudiantes por medio de aplicación en el PEA. La investigación fue dirigida a los estudiantes de Tercero de Bachillerato Informática paralelo “A” del colegio de bachillerato Carmen Mora de Encalada de la ciudad de Pasaje, Provincia El Oro. Dicho esto, se decidió realizar una investigación de enfoque cualitativo y cuantitativo con alcance descriptivo. Los instrumentos empleados para evaluar la efectividad del recurso y desenvolvimiento en el aula fue la aplicación de una encuesta, dirigida tanto al docente como a los estudiantes, logrando así los resultados esperados de una aceptación favorable. Con la ejecución del presente informe de investigación se ha propuesto diagnosticar el impacto del uso correcto de un EVA en la potencialización del PEA, además de un aprendizaje significativo en los estudiantes, donde serán evaluados y obtienen la información necesaria acerca de los contenidos de la asignatura y una interacción directa con el docente, por lo tanto generando motivación e interés por el descubrimiento de las diferentes actividades alojadas en el entorno virtual, esto en el área de informática en el tercer año de bachillerato. Por esta razón se identificó las herramientas utilizadas por el educador en la instrucción de la asignatura aplicaciones ofimáticas en tercero de bachillerato informática para así establecer los recursos adecuados para adecuarlos posteriormente en el entorno propuesto por parte de la investigación. Para ello se realizó el diseño de los contenidos y estructuración de la asignatura aplicación ofimáticas en la plataforma Canvas LMS considerando aspectos importantes que favorezcan el proceso educativo dando importancia a la planificación del docente y el mejor desarrollo e interacción en las clases generando un autoaprendizaje en los estudiantes. Cabe mencionar que la metodología empleada para la ejecución del prototipo fue la metodología PACIE, la cual conlleva el uso de las TIC con beneficio en un aprendizaje significativo, fortaleciendo los contenidos y conocimientos otorgados con la misma. Por consiguiente, se realizó una encuesta y entrevista dirigida al docente Esta primera interacción se realizó de forma presencial con la participación del docente encargado de la asignatura aplicaciones ofimáticas de la institución donde se ejecutó la investigación, se utilizó como instrumento una encuesta realizada con el objetivo de conocer aspectos y sugerencias con el fin de efectuar el perfeccionamiento en cuanto a diseño, estructura, contenido e imágenes en el Eva para la interacción con los alumnos donde se dio a conocer la estructura e información almacenada en el Eva propuesto, además de las actividades planteadas en el entorno con el objetivo de mejorar el desarrollo de contenidos en la asignatura, para determinar las mejoras que se le pueda implementar al recurso digital, para posteriormente aplicarlo a los estudiantes, mediante una clase demostrativa con las diferentes actividades implementadas en el EVA. Después de la primera experiencia con el docente de la asignatura Aplicaciones ofimáticas, se tomaron en cuenta los diferentes aspectos que se debían mejorar para luego realizar la segunda interacción con los estudiantes de tercero de informática, donde se realizó una demostración de las funcionalidades del EVA en la plataforma Canvas LMS, de manera que según los resultados obtenidos se logró identificar la efectividad del uso del EVA en la asignatura y con esto los estudiantes respondieron a favor de la implementación de recurso en la asignatura logrando así los resultados esperados de una aceptación favorable.
Keywords: EVA; MOTIVACION; DESARROLLO DE CONTENIDO; APRENDIZAJE SIGNIFICATIVO